2018
DOI: 10.1016/j.envsci.2017.10.009
|View full text |Cite
|
Sign up to set email alerts
|

How do sectoral policies support climate compatible development? An empirical analysis focusing on southern Africa

Abstract: This is a repository copy of How do sectoral policies support climate compatible development? An empirical analysis focusing on southern Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…This analysis is also important for the African Union's Agenda 2063, which details development objectives for all African states (Africa Union Commission, 2015). Our West African analysis builds on studies of trade-offs and synergies between sector policies and climate compatible development in the Southern African Development Community (England et al, 2018;Stringer et al, 2017) and global analyses of, and guidance for, NDC Implementation Planning (CDKN, 2016;Levin et al 2015;Rogelj et al, 2016). Specifically, the study asks:…”
Section: Introductionmentioning
confidence: 99%
“…This analysis is also important for the African Union's Agenda 2063, which details development objectives for all African states (Africa Union Commission, 2015). Our West African analysis builds on studies of trade-offs and synergies between sector policies and climate compatible development in the Southern African Development Community (England et al, 2018;Stringer et al, 2017) and global analyses of, and guidance for, NDC Implementation Planning (CDKN, 2016;Levin et al 2015;Rogelj et al, 2016). Specifically, the study asks:…”
Section: Introductionmentioning
confidence: 99%
“…Reforestation and agroforestry schemes can help, for instance, to sequester carbon, prevent flooding, enhance biodiversity, rehabilitate degraded lands, provide a local energy supply for the rural poor and improve land use and watershed management [6]. In the water sector, hydropower facilities can reduce fossil fuel use and improve energy security [7]. Obviously, while exploiting the possible synergies mentioned above could offer opportunities for multiple benefits, there can also be trade-offs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Soderberg (2008), Stringer et al (2012) and Kalaba et al (2014) observed that different government sectors or agencies tend to work in isolation, and may produce antagonistic relationships which do not facilitate joint problem solving. When departments work independently, there is a lack of joint learning and long-term alignment of over-arching objectives across departments, resulting in contradictory messages and wastage of resources (England et al, 2018). Coherence in policies can be undermined when interests and policy issues pull in different directions, or they can be reinforced when they are in harmony (May et al, 2006).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Research on policy integration has mostly been devoted to assessing the extent of integration of international agreements into national policies (Stringer et al, 2009;Nilsson et al, 2012;England, Stringer, Dougill, & Afionis, 2018;Atela, Quinn, Minang, Duguma, & Houdet, 2016), while globally, integration of sectoral and departmental policies remains a common challenge (Oberthur, 2009). There is a critical lack of knowledge on the integration of agricultural considerations and issues at sectoral/sub-sectoral levels (Gomar, Stringer, & Paavola, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%